2012
DOI: 10.1007/s10120-012-0179-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with advanced gastric cancer by HER2 status and trastuzumab treatment

Abstract: Background The purpose of this study was to evaluate the impact of human epidermal growth factor receptor 2 (HER2) status and trastuzumab treatment on the prognosis of patients with advanced gastric cancer (AGC). Methods We retrospectively analyzed 364 AGC patients who received systemic chemotherapy. To evaluate the impact of trastuzumab exposure during any type of chemotherapy, our analysis used time-varying covariates to avoid a possible lead-time bias. Results Among the 364 patients, 58 (15.9 %) were HER2-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
60
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(68 citation statements)
references
References 27 publications
5
60
1
2
Order By: Relevance
“…Janjigian et al [16] conducted a retrospective multicenter study examining HER2 expression in 381 Western patients with metastatic gastric or esophagogastric junction cancer, and reported that HER2 overexpression was not an independent prognostic factor. Shitara et al [17] conducted a retrospective study in Japanese patients with unresectable or recurrent gastric cancer, and reported that the OS in 15 HER2-positive patients not receiving trastuzumab treatment was similar to that in 306 HER2-negative patients. Recently, a Chinese prospective cohort study showed that 51 HER2-positive patients receiving trastuzumab had prognoses comparable to those of 251 patients with HER2-negative advanced gastric cancer, whereas 47 HER2-positive patients not receiving trastuzumab had the poorest prognosis [18].…”
Section: Discussionmentioning
confidence: 98%
“…Janjigian et al [16] conducted a retrospective multicenter study examining HER2 expression in 381 Western patients with metastatic gastric or esophagogastric junction cancer, and reported that HER2 overexpression was not an independent prognostic factor. Shitara et al [17] conducted a retrospective study in Japanese patients with unresectable or recurrent gastric cancer, and reported that the OS in 15 HER2-positive patients not receiving trastuzumab treatment was similar to that in 306 HER2-negative patients. Recently, a Chinese prospective cohort study showed that 51 HER2-positive patients receiving trastuzumab had prognoses comparable to those of 251 patients with HER2-negative advanced gastric cancer, whereas 47 HER2-positive patients not receiving trastuzumab had the poorest prognosis [18].…”
Section: Discussionmentioning
confidence: 98%
“…Although some studies have reported that HER2 positivity is a poor prognostic factor in gastric cancer [8][9][10][11], others have found that HER2 has no influence on prognosis [12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to breast cancer in which HER2 is known as a poor prognostic factor [7], the prognostic value of HER2 in gastric cancer is still controversial. Even though some studies have shown that HER2-positivity in gastric cancer is associated with poor outcomes and less sensitive to cytotoxic chemotherapy [8][9][10][11], others have demonstrated that HER2 expression does not influence overall prognosis in gastric cancer [12][13][14][15]. Moreover, it has been getting harder to determine the prognostic value of HER2 per se in AGC after routine prescription of trastuzumab for HER2-positive patients, which can significantly prolong OS [6].…”
Section: Introductionmentioning
confidence: 99%
“…In their study on 231 patients with gastric and gastro-esophageal junction cancer, Tanner et al (7) reported that the presence of HER-2 amplification was associated with short overall survival. In a retrospective study of 364 patients, Shitara et al (21) reported that within HER-2-positive patients, the trastuzumab group had a higher overall survival rate as compared to patients not receiving this medication.…”
mentioning
confidence: 99%